Bleeding risk in patients hospitalized for non-ST-segment elevation acute coronary syndromes in Switzerland: performance of the CRUSADE score. (3rd October 2022) - Wenzl, F; Kraler, S; Raeber, L; Staehli, B E; Roffi, M; Muller, O; Rodondi, N; Camici, G G; Puhan, M A; Rickli, H; Radovanovic, D; Luescher, T F
Abstract: Background: Evaluation of bleeding risk is critical to the management of patients with non-ST-segment elevation acute coronary syndromes (NSTE-ACS). The CRUSADE score is the most established tool to estimate major bleeding events following the index NSTE-ACS. Purpose: We aimed to assess the performance of the CRUSADE score and the predictive utility of the individual score variables in contemporary European populations. Methods: The CRUSADE score was studied in prospectively recruited Swiss patients with NSTE-ACS included in the multicentre SPUM-ACS study (n=4'787) and main findings were validated in the nation-wide AMIS Plus registry (n=46'939). Major bleeding during hospitalization was defined as Bleeding Academic Research Consortium (BARC) class IIIB, IIIC, IV, or V. Discrimination was evaluated by the area under the receiver operating characteristic curve (AUC). Multivariable-adjusted risk ratios (adj RR) were estimated for each of the 8 score variables. Hematocrit estimates were based on hemoglobin concentrations in AMIS Plus. Analyses were performed on complete and imputed data (multiple imputation using chained equations). Results: CRUSADE showed poor discriminatory performance (SPUM-ACS: AUC, 0.65; 95% CI 0.57 to 0.72) and low balanced accuracy (SPUM-ACS: 0.50). Risk predicted by CRUSADE exceeded the observed risk across all predefined risk categories (very low, low, moderate, high, and very high). Decision curve analyses suggested little to no net benefit from using the score. Adjusting for other score variables, signs of heart failure (adj RR, 3.83; 95% CI, 1.93 to 7.37), low hematocrit (adj RR, 2.16; 95% CI, 0.55 to 7.70; <31% vs. >40%), and low systolic blood pressure (adj RR, 2.70; 95% CI, 1.14 to 6.16; <100 mmHg vs. >121 mmHg) were the strongest predictors of major in-hospital bleeds in SPUM-ACS. These findings were similarly observed in AMIS Plus. Conclusion: The CRUSADE score overestimates bleeding risk in NSTE-ACS. Among all 8 score variables, signs of heart failure, low hematocrit, and low systolic blood pressure are the strongest predictors of major in-hospital bleeds in contemporary patients with NSTE-ACS. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Swiss National Science FoundationSwiss Heart Foundation